Doctoral Dissertations on South Asia, 1966-1970 An Annotated Bibliography Covering North America, Europe, and Australia - Shulman, Frank (Michigan Papers On South And Southeast Asia, 2020)
This volume gathers the harvest of recent doctoral dissertations on South Asia, principally from North America and Western Europe, but exclusive of theses from universities in South Asia itself. The yield-1305 dissertations based on research carried out during the early and middle nineteen-sixties and brought to completion between 1966 and 1970-is even greater than one would have guessed, eloquent testimony to the expansion of South Asian studies in the West over the last decade. Doctoral Dissertations on South Asia seeks to be a comprehensive compilation of recently completed theses dealing in whole or in part with the former civilizations and the contemporary affairs of Ceylon, India, Nepal and Pakistan. At the same time, this work provides striking testimony of the dynamic growth of Asian Studies outside the subcontinent and particularly in the United States, Great Britain, Germany and France, where most of the major centers of scholarship are presently found. It is an interdisciplinary work covering the natural sciences as well as the humanities and social sciences.